Assembly of Gold Nano Particles on a Modified Glass Silicone Surface - Shashidhar; Ramprasad; Basavaraja, C.; Vishnuvardhan, T.K. (Asian Journal of Chemistry, 2012)
Recent development in the field of technologies has pushed towards miniaturization of materials on the nanometer levels which are critical and encouraging to design of new nanoscale materials systems which is having a novel and/or enhanced properties without resorting to new synthetic chemistry with the associated environmental and cost issues. In order to discuss these issues an effort was made to describe a facile method for stabilizing gold nano-particles over a modified cover glass surface layers of dimension 18 mm × 18 mm samples. In this study, the different sized gold nano-particles were synthesized by standard methods. The modified glass surfaces containing assembled gold nano-particles were analyzed by scanning electron microscopy, transmission electron microscopy, atomic force microscpy and other spectral studies. With this method, uniformly shaped rods with high aspect ratio can be prepared and assembled.